Origin of ultra-compact dwarfs: a dynamical perspective. Issue Volume 10:Issue S312(2014) (7th March 2016) - Zhang, Hong-Xin; Peng, Eric W.; Côté, Patrick; Liu, Chengze; Ferrarese, Laura; Cuillandre, Jean-Charles; Caldwell, Nelson; Gwyn, Stephen D. J.; Jordán, Andrés; Lançon, Ariane; Li, Biao; Muñoz, Roberto P.; et al.
Abstract: Discovery of ultra-compact dwarfs (UCDs) in the past 15 years blurs the once thought clear division between classic globular clusters (GCs) and early-type galaxies. The intermediate nature of UCDs, which are larger and more massive than typical GCs but more compact than typical dwarf galaxies, has triggered hot debate on whether UCDs should be considered galactic in origin or merely the most extreme GCs. Previous studies of various scaling relations, stellar populations and internal dynamics did not give an unambiguous answer to the primary origin of UCDs. In this contribution, we present the first ever detailed study of global dynamics of 97 UCDs ( r h ≳ 10 pc) associated with the central cD galaxy of the Virgo cluster, M87. We found that UCDs follow a different radial number density profile and different rotational properties from GCs. The orbital anisotropies of UCDs are tangentially-biased within 40 kpc of M87 and become radially-biased with radius further out. In contrast, the blue GCs, which have similar median colors to our sample of UCDs, become more tangentially-biased at larger radii beyond 40 kpc. Our analysis suggests that most UCDs in M87 are not consistent with being merely the most luminous and extended examples of otherwise normal GCs. The radially-biased orbital structure of UCDs at large radii is in general agreement with the scenario that most UCDs originated from the tidally threshed dwarf galaxies.